Analisis pengaruh mekanisme good corporate governance, leverage, dan ukuran perusahaan terhadap tindakan manajemen laba pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2014-2016 - Selviani, Selviani; Widjaja, Indra (Universitas Tarumanagara, 2017)
The purpose of this research is to test the influence of good corporate governance mechanisms, leverage, and firm size on earnings management. This research applies good corporate governance mechanisms (with the proxy of managerial ownership, independent commissioner on the board, and audit committee), leverage, and firm size as independent variables, and earning management as dependent variable. The subject of the research is the manufacturing companies (limited to the consumer goods industry sector) which are listed in the Indonesia Stock Exchange from 2014 to 2016. The sample selection is performed by using the purposive sampling method. From this method, it was collected 84 observations from 28 companies during 3 years. By using multiple regression analysis as the research method, the results show that leverage and firm size have influenced earnings management, while good corporate governance mechanisms don’t influence earnings management.